(untitled) (Research, Society and Development, 2022)
The aim of this text is to highlight the conditions in which the use of marine resources happens into the Todos o Santos Bay (BTS) and the environmental impacts caused. The BTS is a coastal area of considerable dimensions in which there is a growing intensification of interventions aimed at transport infrastructure and for entertainment and summer housing. In its elaboration, a review of the academic literature on the subject was used, official data on economic and environmental impacts were utilized and the possibility of applying the Ecological Modernization Theory (EME) to the problem was analyzed, seen as a possible mediator of conflicts existing among several uses of BTS’ marine resources. It is expected that it will be useful in the elaboration of local public policies and in the creation of joint efforts on the part of governments and civil society aiming at the marine and coastal preservation of the BTS.